Pengembangan model workplace learning (WPL) untuk meningkatkan kompetensi keahlian jasa boga siswa program studi tata boga SMK pariwisata - Yulia Rahmawati; As'ari Djohar (Inovasi Kurikulum, 2015)
Vocational practical learning activities are an important part, however, they do not link the practice learning activities conducted in schools with field work in the industry, yet. The implementation of the vocational students' field industrial practice (prakerin) still cause some problems and complaints from industry. Research results show that the pace of learners' work is slow, work accidents is still high, lack of responsibility sense, less able to maintain hygiene in food handling, as well as less neat of personal appearance. The purpose of this study attempts to develop WPL model to improve the student's catering competency skill of Tourism Culinary Vocational School. This research was done by conducting Research and Development (R & D) towards the Catering Tourism Culinary Vocational School students. The process started from preliminary studies, model development and validation done by the experts. The results show that: (1) preliminary (a) there is variation in the planning, implementation, evaluation activities in vocational industrial working practices studied, (b) the condition of infrastructure in vocational is relatively adequate, (c) the timing of the practice in the industry starts from 3-6 months. (2) WPL Model covers the planning, implementation, and evaluation. After the draft of WPL models developed and (3) the results of the validation test show that WPL model is effective for improving the students' competence of vocational catering skills. The author proposes some recommendations, namely: the monitoring and evaluation done by knowledge ability, work attitude (employability skill), and the process of interaction in the workplace using complete learning device. This study is limited to WPL Model of Students' Catering Competency Skill of Tourism Culinary Vocational School. Other researchers who are interested in the model are recommended to develop the WPL model of vocational school cooperate with the relevant industry.